ICT, Energy Intensity, and CO2 Emission Nexus - Bildirici, Melike E.; Castanho, Rui Alexandre; Kayikci, Fazil; Genc, Sema Yilmaz (MDPI, 2022)
The relationship between information and communication technology investment (ICT), environmental impacts, and economic growth has received increasing attention in the last 20 years. However, the relationship between ICT, energy intensity, environmental impacts, and economic growth was relatively neglected. In this paper, we aimed to contribute to the environmental literature by simultaneously analyzing the relationship between ICT, energy intensity, economic growth, Carbon dioxide (CO2) emissions, and energy consumption for the period of 1990-2020 in G7 countries. We employed the Panel Quantile Auto Regressive Distributed Lag (PQARDL) method and Panel Quantile Granger Causality (PQGC) methods. According to the results of PQARDL method, energy consumption, ICT, CO2 emission, and energy intensity have effects on economic growth in the long and short run. According to the of PQGC methods allowing causality results for different quantiles, there is evidence of a bidirectional causality between ICT investment and economic growth for all quantiles and evidence of a unidirectional causality from ICT to energy consumption and from CO2 emissions to ICT investment and energy efficiency. Our results indicate that the governments of the G7 countries have placed energy efficiency and ICT investment at the center of their policies while determining their environmental and energy policies, since energy consumption is a continuous process.
Keywords: information and communication technologies (ICT) investment; energy intensity; economic growth; CO2 emissions and energy consumption; Panel Quantile Auto Regressive Distributed Lag method; Panel Quantile Granger Causality methods; ECONOMIC-GROWTH; TELECOMMUNICATIONS INFRASTRUCTURE; COMMUNICATION TECHNOLOGY; ELECTRICITY CONSUMPTION; QUANTILE REGRESSION; INFORMATION; INVESTMENT; MODEL; Energy & Fuels